PENGARUH PROBLEM BASED LEARNING BERBANTUAN MEDIA KOMET QR TERHADAP KEMAMPUAN PEMECAHAN MASALAH GEOMETRI KELAS IV GUGUS BUDI UTOMO MIJEN SEMARANG - Imawati, Siti Siyam Irma; Andrijati, Noening (INSPIRAMATIKA, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Komet QR media on the problem-solving abilities in geometry of fourth-grade students at the Budi Utomo Cluster, Mijen, Semarang. The research employed a quantitative approach with a quasi-experimental design. The subjects consisted of two classes: the experimental class, which used the Problem-Based Learning model assisted by Komet QR media, and the control class, which used conventional learning methods. Data were collected through pretests and posttests to measure students' problem-solving abilities. The data were analyzed using t-tests and gain score analysis. The result of the n-gain test was 0.6512, which falls into the medium category, indicating a significant difference in problem-solving ability between students who learned using Problem-Based Learning assisted by Komet QR and those who did not. This is further supported by the average posttest scores, with the control class scoring 68 and the experimental class scoring 81.